New technologies in the fieldof sensory marketing and customer experience:a systematic literature review - Dawid Gajda (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Nowadays, we are noticing more and more new technological solutions that fit into the field of sensory marketing, the implementation of which is in a relatively preliminary stage. They are intended to improve customer experience. The main objective of the research is to determine the main topics covered in the literature. This article covers a systematic literature review of research conducted to date on new technologies that are part of the field of sensory marketing related to customer experience. The research search was based on two databases: Scopus and Web of Science Core Collections. Studies conducted between 2007 and May 2022 were included. Four inclusion criteria were used: database, terms, language, and cover period. No methods were used to assess the risk of bias in the included studies. 33 items of literature were qualified for qualitative synthesis. Based on the analysis, a conceptual framework of the most commonly used antecedents and outcomes in research was created, and two main research areas were identified: sense of telepresence and research by technology type. In view of this, further research directions based on the identified research gaps were indicated.